2016
DOI: 10.19044/esj.2016.v12n5p393
|View full text |Cite
|
Sign up to set email alerts
|

Citizen's Adoption Of Mobile Land Record Information Systems (mLRMIS): A Case of Pakistan

Abstract: By implementing a prolonged social cognitive theory (SCT) this article investigates factors including outcome expectation, affect, anxiety, self-efficacy, social influence, trust, facilitating conditions, e-satisfaction, information quality and e-service quality impacting citizen’s intention to adopt a mobile based e-government system called mobile Land Record Information Systems (mLRMIS) with respect to Pakistan. The prolonged social cognitive theory (SCT) was actually affirmed by analyzing gathered data peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 68 publications
(51 reference statements)
2
3
0
Order By: Relevance
“…Hence, H4 was not supported, while H4a was supported. Malik et al [55,56] found that perceived usefulness is influenced by an understanding of the information quality; [83] the current study analysis also revealed similar findings (H2b). Machdar and Malik et al [55,56,84] found that the quality of information positively affects perceived usefulness and ease of use, and perceived ease of use positively affects perceived usefulness [84].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Hence, H4 was not supported, while H4a was supported. Malik et al [55,56] found that perceived usefulness is influenced by an understanding of the information quality; [83] the current study analysis also revealed similar findings (H2b). Machdar and Malik et al [55,56,84] found that the quality of information positively affects perceived usefulness and ease of use, and perceived ease of use positively affects perceived usefulness [84].…”
Section: Discussionsupporting
confidence: 81%
“…Malik et al [55,56] found that perceived usefulness is influenced by an understanding of the information quality; [83] the current study analysis also revealed similar findings (H2b). Machdar and Malik et al [55,56,84] found that the quality of information positively affects perceived usefulness and ease of use, and perceived ease of use positively affects perceived usefulness [84]. Several studies have found strong relationships between perceived usefulness and self-reported use [85], extent of use [86], or dependence on an information system [87].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This theory also points out that information acquisition is a process of thinking emotions and behavioral interaction of individuals, and individual differences such as knowledge reserve, experience, and social network relationship of information collectors all affect information acquisition ability (Wilson, 1999 ). Several studies in the literature employ cognitive-behavioral theory from different perspectives to measure the cognitive behavior of individuals and is considered a key aspect of organizational decision-making, i.e., in entrepreneurship (Shahzad et al, 2021 ), technology adoption decisions (Park and Kim, 2014 ; Malik et al, 2016 ; Zhang, 2019 ), social media and consumer behavior (Wang and Lin, 2012 ; Wang et al, 2019 ). Therefore, considering the importance of this theoretical aspect, we use it as the underlying theory for determining the strategic decision-making behavior of an organization's green innovation.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%